IMF-supported adjustment programs: Welfare implications and the catalytic effect - Carlos De Resende (Bank of Canada, 2007)
The author studies the welfare implications of adjustment programs supported by the International Monetary Fund (IMF). He uses a model where an endogenous borrowing constraint, set up by international lenders who will never lend more than a debt ceiling, forces the borrowing economy to always choose repayment over default. The immediate potential welfare cost of joining a program is driven by IMF conditionality: to be able to borrow from the IMF, the country has to submit to limits on the consumption of public goods. The benefits derive from the additional borrowing from the IMF (at a lower interest rate) and/or through a "catalytic effect" on private loans, which facilitates consumption smoothing over time. Simulations of the dynamic model in two institutional environments - with and without the IMF - are compared. Results indicate that when conditionality forces the country to save more, at a cost that does not prevent it from joining an IMF program, the resulting lower probability of default can induce private lenders to relax their borrowing constraints. Based on a calibration of the model for the Brazilian economy, the overall welfare gains associated with IMF programs are relatively small.
Keywords: F32; F33; F34; F41; 330; Internationale Wirtschaftshilfe; Internationaler Kredit; Verschuldungsrestriktion; Wohlfahrtseffekt; Wirtschaftsmodell; Brasilien